2019
DOI: 10.1016/j.pec.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The Taxonomy of Everyday Self-management Strategies (TEDSS): A framework derived from the literature and refined using empirical data

Abstract: The TEDSS Framework may help to guide health service delivery and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 27 publications
0
57
1
3
Order By: Relevance
“…However, another important system indicator that is absent from the current life satisfaction literature is avoidable hospitalisations, such as those caused by ACSCs. Given the evidence around the interrelationships between emotional factors and chronic disease self -management14 and in particular how emotional and psychological distress can influence the ability of a patient to manage their chronic condition,15 16 more research is needed that quantitatively measures the impact of subjective well-being on important healthcare system outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, another important system indicator that is absent from the current life satisfaction literature is avoidable hospitalisations, such as those caused by ACSCs. Given the evidence around the interrelationships between emotional factors and chronic disease self -management14 and in particular how emotional and psychological distress can influence the ability of a patient to manage their chronic condition,15 16 more research is needed that quantitatively measures the impact of subjective well-being on important healthcare system outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of a recent review of 28 interventions, eight reported no specific theoretical foundations, ten used Bandura's social cognitive theory as principle, while the rest provided a wide variety of other theoretical underpinnings, [6] very few of them explicitly describe how this is conceptualized or even how to measure it directly [7,8] let alone programs aimed at the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is still needed. [6][7][8][9][10][11][12] One of the most reported programs in chronic condition management was developed at Flinders-Australia University, which conceptualizes self-management and measures this through the Partners in Health Instrument (PHS). The PIH concept describes 6 characteristics of this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 26 27 While the scoping review found that 13 of the 28 measures were multidimensional, none of them captured the range of domains important to patients, as identified by the TEDSS. 19 Lack of sufficient specificity for individualised patient care and self-management research Single-score measures can be brief, reliable and valid instruments for screening, risk prediction and for use in outcome studies 28 but they have limited utility in differentiating individual patients' self-management support needs or in personalising or tailoring care. A Cochrane review (19 studies n=10 856 participants) concluded that when compared with usual care, personalised care planning leads to improvements in 'physical and psychological health status, and peoples' capacity to self-manage their condition'.…”
mentioning
confidence: 99%